THE EFFECT OF MOTIVATION AND WORK WAGES ON EMPLOYEE PERFORMANCE IN THE PROTOCOLER DIVISION AT THE OFFICE OF THE REGENT OF BATANG HARI, JAMBI - Khoiroh, Nadiatul; Siswati, Etty; Zamy, Lailatul (International Journal of Multidisciplinary Research and Literature, 2025)
The purpose of this research is to elucidate the impact of motivation and wages on employee performance in the protocol section of the Batang Hari Jambi Regent's Office. The quantitative descriptive approach employs multiple linear regression analysis tools. The influence of Motivation (X1) and Wages (X2) as independent variables on Employee Performance (Y) was tested using the t-test, F-test, and coefficient of determination. The results of hypothesis testing on the Motivation variable (X1) show that the value of Tcount (4.173) < Ttable (2,036). The results of hypothesis testing on the variable Wage (X2) show that the value of Tcount (17,541) is greater than Ttable (2,036). From the partial test results, it is found that Price (X1) and Wage (X2) influence Employee Performance (Y). Simultaneous variable testing reveals that the value of Fcount is greater than Ftable, or 362.644 is greater than 3.30, indicating that Motivation (X1) and Wages (X2) simultaneously influence Employee Performance (Y). The Adjusted R-Square value is 0.956 for Y, or 95.6%, and the remaining 4.4% is influenced by other variables not examined in this research.